Sport and exercise in times of self-quarantine: How Germans changed their behaviour at the beginning of the Covid-19 pandemic - Mutz, M.; Gerke, M. (International Review for the Sociology of Sport, 2020)
Due to the massive spread of a new Coronavirus (SARS-CoV-2), many European governments enacted rules and legislations in order to reduce social interactions and contain the spread of the virus. German authorities put in force a lockdown of all non-essential infrastructure, starting on 22 March 2020. These policies included the closing of sports clubs, fitness centres and community sports grounds. Most federal states prohibited social gatherings of more than two people, thereby further restricting opportunities to play sport and exercise together. The paper addresses how Germans adapted their leisure time sport and exercise (LTSE) activities in this unprecedented situation. Based on survey data representing the adult population ( 14 years, N=1001, data collection 27 March to 6 April 2020), the paper shows a significant decline in LTSE activities at population level. Overall, 31% of Germans reduced their LTSE, while 27% maintained and 6% intensified their LTSE level. A share of 36% was not engaged in LTSE, either before or at the beginning of the lockdown. Younger age groups were more likely to maintain LTSE levels compared with older ones. Comparisons of `reducers` and `maintainers/ intensifiers` indicate that the latter group increased home-based workouts and outdoor endurance sports, while `reducers` did not find adequate substitutes for their sporting routines.